Analisis Granular Dan Hialin Pada Udang Kaki Putih (Litopenaeus vannamei) Dengan Pemberian Asam Lemak DHA (Docosahexaenoic acid) - Siregar, Kelly Aurora; Br Sitepu, Gressty Sari; Fain, Hamdanul (Universitas Bangka Belitung, 2024)
White Leg shrimp have a non-specific immune response that can be seen in granular cells and hyaline cells. To support an excellent white-leg shrimp immune response, providing an immunostimulant in the form of docosahexaenoic acid (DHA) is necessary. This research activity aims to determine the percentage of granular and hyaline cells in white-leg shrimp and the immune response of white-leg shrimp. This research was carried out in April 2022 at PT. Emas Sempurna Anugrah, Bangka Belitung. This type of research is descriptive qualitative. There are five ponds studied with different pond sizes and stocking densities. The results showed that the percentage of granular cells is higher than hyaline cells, with an average percentage of granular cells is 57.27%, while the average percentage of hyaline cells is 42.73%. The average THC value is 5,730,000 cells/ml, indicating that the white-leg shrimp's immune response is good but has fluctuating value. The white-leg shrimp's immune response in the pond shows inconsistent results due to external factors such as water quality and bad weather.